Management of shock in trauma. Issue 8 (August 2017) - Boyd, Matthew; Keene, Damian D.
Abstract: Shock is defined as the failure of the circulatory system to provide the organ perfusion and tissue oxygenation required to meet cellular metabolic demands. Traumatic shock is most commonly associated with haemorrhage, although non-haemorrhagic shock can be found in trauma in the form of cardiogenic or neurogenic shock. Over the last decade evidence has demonstrated that trauma patients have an acute traumatic coagulopathy (ATC) caused by the injury process itself. This has been fundamental to the development of the current approach to management of traumatic shock, known as damage control resuscitation (DCR). DCR encompasses three key resuscitative strategies, permissive hypotension, haemostatic resuscitation (the use of blood products as primary resuscitative fluids) and damage control surgery. The implementation of DCR alongside the creation of trauma networks has been revolutionary in the management of the shocked trauma patient. Current focus is on evolving and refining these strategies including identifying the subsets of patients at greatest risk as early as practicable following injury.